Reducing the wastage of fresh frozen plasma in a hospital blood bank through the use of Six Sigma principles. Issue 28 (1st October 2022) - Hester, Robert Harrison; Castillo, Estella; Casteel, Kelly; Natividad, Lorenz; Aung, Fleur M.; Martinez, Fernando; Vadhan-Raj, Saroj
Abstract : 45 Background: MD Anderson Cancer Center is one of the largest users of blood products in the United States, with approximately 3, 600 units of blood (PRBCs) transfused per month, and over 500 units of fresh frozen plasma (FFP) transfused per month. The wastage of blood products has both financial and patient care implications, as well as implications to donors. Decreasing blood product wastage is an institutional priority in terms of both resource utilization and cost savings. Methods: Outside metrics for the waste of blood products published by the American Association of Blood Banks (AABB) were compared to current data on the percentage wastage of blood products for fiscal year 2020. A dedicated project team set an aim to reduce the wastage of FFP by 25% from Q4 2020 to Q3 2021. Using Six Sigma principles, a run chart was developed to track units FFP ordered and transfused from October 2020 – March 2021. Minitab software was used to calculate mean FFP ordered, the upper confidence interval, as well as 2 standard deviations above the mean to determine a new maximum FFP thaw level. Results: The historical FFP "thaw level" was 32 units of FFP thawed per day. From October 2020 – March 2021, the average number of FFP units ordered per day was 8. The upper confidence level was 32, and 2 standard deviations was 24 units. After identifying 3 data points that were "out of control" and unrepresentative of actual usage, these values were adjusted to 7.5 units and 19.5 units, respectively. Based on this data, the daily thaw level was adjusted from 32 units per day to 20 units per day on June 21 st 2021. As of Q3 2021, this has resulted in a 40.7% decrease in the wastage of FFP. Conclusions: The application of Six Sigma principles was an effective way to identify variation in the ordering of fresh frozen plasma (FFP), and allowed for a sizeable reduction in the daily thaw level of this blood product. Post-intervention, there has been a dramatic decline in the wastage of FFP, resulting in cost savings for our institution and better stewardship of this scare resource.